Inventarisasi Jenis-jenis Rumput di Jalur Pendakian Gunung Ungaran - Nuhaa, Muhammad Hasiibun; Lianah, Lianah; Wahidah, Baiq Farhatul (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2019)
Mount Ungaran has very varied vegetation which includes grass plants. The purpose of this study was to find out the types of Poaceae family grass found on the Mount Ungaran hiking path. This type of research is a qualitative research field. The object of the research is the types of grass belonging to the family Poaceae. Data collection techniques used in this study were observation and characterization. The results of the study obtained 29 species from 23 genera.